Structural engineering of carbon nitride for enhanced photocatalytic degradation and adsorption of environmental pollutants - Meie Zheng; Junbo Du; Fei Ma; Wenwen Li; Yujia Shao; Xinyue Gao; Mengru Guo (Results in Chemistry)
Since the emergence of the field of photocatalytic water splitting in 2009, the application potential of graphitic carbon nitride (g-C3N4) in the field of environmental remediation has been explored. However, to further enhance its adsorption and photocatalytic degradation performance toward typical organic pollutants, a deep understanding of the crucial role of structural regulation is still needed. In response, this review systematically summarizes the cutting-edge strategies for the structural optimization of g-C3N4, focusing on various methods such as nonmetallic element doping, vacancy defect construction, edge defect regulation, and the synergistic combination of multiple defects. It also delves into the mechanisms by which innovative strategies, including framework structure design and protonation, significantly enhance the ability of a material to capture environmental pollutants such as methylene blue (MB) and its photocatalytic degradation efficiency, revealing the essence of performance enhancement at the micro level. Finally, this review highlights the key achievements of advanced characterization techniques such as electron spin resonance (ESR) and transient photoinduced voltage (TPV) methods. This review aims to provide researchers with an in-depth analysis of the relationship between the structure and properties of g-C3N4 materials, offering a solid theoretical foundation and innovative experimental ideas for their application in environmental pollution control, especially in the development of efficient and sustainable pollutant removal technologies.